(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Education is theright of every child because it equips him to meet the challenges of life. Thechildren with disabilities (CWD) need this all the more, to supplement theirdifferential talents so that they can prepare themselves for a happy productiveand useful life. Efforts to educate children with disabilities began soon afterindependence in India. An attempt has been made to examine the policies andlegislations for educating the children with disabilities in India after post-constitution era. In the final section, challenges for providing education toCWD and in that light some recommendations were made.